Integration of Digital Marketing, Financial Technology, and Green Innovation on the Performance of Surabaya's Culinary MSMEs - Syammakh, Zayyan Adyatma; Fazlurrahman, Hujjatullah; Abbrori, Nanang Hoesen Hidroes; Rahman, Muhammad Fajar Wahyudi (SAFE-Network, 2026)
This study aims to analyze the influence of digital marketing, financial technology (fintech), and green innovation on the performance of Micro, Small, and Medium Enterprises (MSMEs) in the food and beverage (culinary) sector in Sukomanunggal District, Surabaya. This study was motivated by the inconsistency of previous studies, which showed that the three variables had both significant and insignificant effects on MSME performance. In this context, the study offers a new approach by focusing on a region where business actors are relatively more adaptive to digitalization and environmentally friendly innovation. Using a quantitative approach and purposive sampling technique, data were collected from 50 MSMEs that have implemented digital marketing, financial technology (fintech), and green innovation. The results of this study indicate that the simultaneous combination of digital marketing, fintech, and green innovation can drive improved performance among MSMEs, measured through customer growth, revenue, operational efficiency, and market expansion. These findings are expected to provide practical contributions for MSME actors and enrich the academic literature in the field of digital business strategy and sustainability.